2012
DOI: 10.1111/j.1365-2443.2012.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired retrograde membrane traffic through endosomes in a mutant CHO cell defective in phosphatidylserine synthesis

Abstract: Phosphatidylserine (PS), a relatively minor constituent in the plasma membrane (PM), participates in various cellular processes such as clearance of apoptotic cells and recruitment of signaling molecules. PS also localizes in the membranes of endocytic organelles, such as recycling endosomes (REs). We recently showed that in REs, PS binds to the pleckstrin homology (PH) domain of evectin-2, thereby regulating retrograde traffic from REs to the Golgi. However, direct evidence that PS has a role in retrograde tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
(28 reference statements)
2
40
0
Order By: Relevance
“…1G). This reduction is comparable to the reduction in PtdSer levels observed in PSA-3 cells, which are defective in PtdSer synthesis when cultured in the absence of ethanolamine (22) (Fig. 1G).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1G). This reduction is comparable to the reduction in PtdSer levels observed in PSA-3 cells, which are defective in PtdSer synthesis when cultured in the absence of ethanolamine (22) (Fig. 1G).…”
Section: Resultssupporting
confidence: 64%
“…Total cellular lipids were isolated by Folch extraction (21). Lipid extracts, along with pure lipid standards, were spotted onto a high performance one-dimensional thin-layer chromatography (TLC) silica gel plate (catalog number 1057150001; EMD Millipore) and resolved by using methyl acetate-chloroform-1-propanolmethanol-1% aqueous KCl (25:25:25:10:9, vol/vol/vol/vol/vol) (22). After iodine labeling, lipid spots were cut out and quantified by phosphate analysis as described previously (23).…”
mentioning
confidence: 99%
“…For instance, in mammalian cell pulse-chase experiments, TGN38 and Shiga toxin have been shown to be retrograde cargos that traverse the recycling endosome en route to the TGN (20,21,25). Canonical recycling endosome regulators Rab11, FIP1/RCP, and mRme-1/EHD1 have been shown to be important regulators of recycling endosome-to-TGN transport of retrograde cargo (23,25,54).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CHO cell pulse-chase analysis of fusion proteins bearing the transmembrane and intracellular domains of retrograde recycling proteins, TGN38 and Furin, showed that TGN38 trafficked from the early endosome to recycling endosome to the Golgi, whereas Furin recycling involved transit from the early endosome to the late endosome to the Golgi (20,21). TGN38 and Shiga toxin have been shown to require distinct sets of SNARE proteins to complete transport to the Golgi, also indicating that different cargos recycle to the Golgi in different types of vesicles (22).…”
mentioning
confidence: 99%
“…To further investigate the role of PS in mediating spatial cross talk between different Ras isoforms, we manipulated PM PS levels using a CHO mutant cell line, PSA-3, which lacks PS synthase 1 (PSS1) and is an ethanolamine auxotroph (38). Interestingly, the level of PS on the PMs of parental CHO cells was also dependent on the ethanolamine content of the culture media (Fig.…”
Section: Ras Nanoclusters Have Different Lipid Compositions But All mentioning
confidence: 99%